An " Academic Review and Critique of Gender Dynamics and Life Insurance Uptake in Ghana: A Study of the 2018 Publication by Ampaw et al." - Maalila Malambo (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The study conducted by Ampaw et al. titled “Gender perspective on life insurance demands in Ghana" examines the factors affecting the adoption of life insurance by male and female household heads. Their findings suggest that women in Ghana purchase more life insurance products than men, which may be useful for insurers in maximizing profits. However, the study overlooks critical considerations such as claim costs, administrative expenses, and profitability. While the authors' unique focus on gender dynamics is noteworthy, they did not consider household size, literacy levels, premium costs, and government incentives for women to purchase policies. Prior research indicates that education, awareness, income, and employment are key determinants of life insurance uptake in Ghana, which contrasts with the authors' findings. Further research is necessary to examine the relationship between insurance and customer value or profitability. In conclusion, while Ampaw et al.'s research adds to the scarce literature on life insurance demand in Africa, it lacks practicality and ignores significant factors. Additional research is necessary to comprehend the determinants of life insurance uptake in Ghana and insurance's role in customer value and business profitability in Africa. JEL classification codes for this article could include: G22: Insurance; Insurance Companies; Actuarial Studies J16: Economics of Gender; Non-labor Discrimination O55: Africa; Insurance and Insurance Markets